Density-dependence tips the change of plant–plant interactions under environmental stress - Ruichang Zhang (Nature Portfolio, 2020)
Density-dependence is rarely accounted for in plant-plant facilitation studies. Here the authors develop a framework that incorporates density-dependence in the stress-gradient hypothesis, and test it first through modeling and then empirically on Arabidopsis thaliana along salt stress gradients.